2002
DOI: 10.1089/088922202753394664
|View full text |Cite
|
Sign up to set email alerts
|

Coreceptor Utilization of HIV Type 1 Subtype E Viral Isolates from Thai Men with HIV Type 1-Infected and Uninfected Wives

Abstract: HIV-1 coreceptors CCR5 and CXCR4 play an important role in viral entry and pathogenesis. To better understand the role of viral tropism in HIV-1 transmission, we examined the coreceptor utilization of viral isolates obtained from men enrolled in a study of heterosexual transmission in northern Thailand. Viral isolates were obtained from HIV-1-positive males who had either HIV-1-infected spouses (RM; n = 5) or HIV-1-uninfected spouses (HM; n = 10). Viral isolates from 1 of the 5 RM males and 2 of the 10 HM male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…Another explanation is that HW were exposed to defective or replication-incompetent viruses that generated less envelope, and therefore fewer processed antigens, for presentation to T cells. However, initial studies of viruses isolated from the HM and RM indicated that all viruses were equally capable of infecting PBMCs (Butera 2002, personal communication) and that all had similar coreceptor usage profiles [39,46]. Thus, there is no evidence that the transmitting viruses had abnormal phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation is that HW were exposed to defective or replication-incompetent viruses that generated less envelope, and therefore fewer processed antigens, for presentation to T cells. However, initial studies of viruses isolated from the HM and RM indicated that all viruses were equally capable of infecting PBMCs (Butera 2002, personal communication) and that all had similar coreceptor usage profiles [39,46]. Thus, there is no evidence that the transmitting viruses had abnormal phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the frequency of subtype C X4 viruses will increase over time or will remain relatively low compared to that of subtype B infections remains to be determined. An analogy can be made to the HIV-1 subtype E epidemic in Thailand; there, early isolates were mostly of the NSI phenotype, but as the epidemic progressed, SI viruses started to appear with ever-increasing frequency (13,30,48,49,57). Further studies on subtype C infection may reveal the same trend.…”
Section: Sensitivity Of Subtype C Isolates To Ccr5 and Cxcr4 Inhibitomentioning
confidence: 98%
“…Although some studies have found no difference in phenotype among different subtypes (10,47,56), others have reported a trend for an unequal distribution of SI versus non-syncytiuminducing (NSI) viruses among different subtypes (1,5,17,35,39,(49)(50)(51)(52)57). One study (5) found that subtype D and CRF01_AE viruses were predominantly CXCR4-using (SI), whereas subtype A and C viruses were predominantly CCR5-using (non-SI, NSI).…”
mentioning
confidence: 99%